Conditions for the career development of young people with higher education from a regional perspective - Szydlik-Leszczyńska, Agata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Changes taking place in the contemporary world have stimulated a faster development of knowledge and have led to the need for businesses to adjust to them, including in their expectations towards their employees. Employees and young people have entered a higher level on a larger scale, which has consequently resulted in an influx of a large number of people with higher education into the labour market. The aim of this study is to present the regional conditioning of professional careers and the perspectives for their development based on the case of young people with higher education in the Świętokrzyskie voivodeship. The term professional career has been presented, as well as its stages, the situation of young people, including those with higher education, and factors limiting its development in the region. A professional career is a crucial element in the lives of contemporary humans. It determines their status and, thanks to it, they can develop and fulfil their ambitions. However, the development of a career is hindered in smaller and less developed communities, where there is a shortage of workplaces for people with higher education. It forces young people to migrate to large cities of a metropolitan character, where there are better possibilities of development and higher earnings. This results in a deficit of valuable human capital and in the deepening of the hard demographic and economic situation in the problem region. The article is of a cognitive character, with its research methods being literature studies and statistical data analysis. In order to achieve full comparability, the following study is based on the data available until the end of 2017 because there is some shortage of data for the Świętokrzyskie voivodeship in the following years.

Zmiany zachodzące we współczesnym świecie spowodowały szybszy rozwój wiedzy i wymusiły dostosowania przedsiębiorstw do tych zmian, w tym związane z wymaganiami wobec pracowników. Pracownicy i młodzi ludzie na dużą skalę zaczęli kształcić się na poziomie wyższym, co w konsekwencji doprowadziło do napływu dużej liczby osób z wyższym wykształceniem na rynek pracy. Celem opracowania jest zaprezentowanie uwarunkowań regionalnych kariery zawodowej i perspektyw jej rozwoju na przykładzie osób młodych z wyższym wykształceniem w województwie świętokrzyskim. Przedstawiono pojęcie kariery zawodowej, jej etapy, sytuację osób młodych, w tym z wyższym wykształceniem oraz czynniki ograniczające jej rozwój w regionie. Kariera zawodowa jest istotnym elementem życia współczesnego człowieka. Stanowi o jego statusie, dzięki niej może się rozwijać i realizować własne ambicje. Rozwój kariery jest jednak utrudniony w mniejszych i słabiej rozwiniętych ośrodkach, gdzie istnieje niedobór miejsc pracy dla osób z wyższym wykształceniem. Powoduje to, że osoby młode migrują do dużych ośrodków o charakterze metropolitalnym, gdzie są większe możliwości rozwoju i zarobkowania. Skutkuje to ubytkiem wartościowego kapitału ludzkiego i pogłębianiem trudnej sytuacji demograficznej i gospodarczej w regionie problemowym. Artykuł ma charakter poznawczy, jako metody zastosowano studia literaturowe i analizy danych statystycznych. W celu uzyskania pełnej porównywalności opracowanie opiera się na danych dostępnych na koniec 2017 roku, ponieważ występują pewne braki danych dla województwa świętokrzyskiego za lata kolejne.
Keywords: professional career; perspectives of development; problem region; kariera zawodowa; perspektywy rozwoju; region problemowy